ANALISIS KONSUMSI BAHAN BAKAR SPESIFIK PADA KONDISI PEMBEBANAN MAKSIMAL - Rezza Amanda; Yovan Witanto; A. Sofwan F Alqap (UNIB Press, 2026)
The operational performance of a Gas and Steam Power Plant (PLTGU) is largely determined by its cycle thermal efficiency. Specific fuel consumption (SFC) is a key metric that represents the ratio of total fuel consumption to generated electrical power. This study aims to analyze the SFC value and its tendency towards maximum load. The method used is quantitative by processing steady-state operational data from the central control room (CCR). Data were taken under operating conditions with natural gas fuel and maximum load. The calculation results show a very narrow and stable variation in SFC values, ranging from the lowest to 0.30769 kg/kWh at a load of 19.88 MW to the highest at 0.30967 kg/kWh at a load of 20.01 MW. Theoretically, efficiency (indicated by a decrease in SFC) should increase with increasing load. The anomalous increase in SFC at 20.01 MW at 10:00 a.m. Western Indonesian Time (WIB) is interpreted as a result of the fuel injection system's rapid response to the sudden increase in load, or the engine operating slightly outside its design efficiency range at that point. Nevertheless, the overall trend shows stable efficiency, with a tendency for SFC to decrease with increasing load, indicating the unit is capable of maintaining optimal performance under peak load conditions.